CD4+ Memory Stem T Cell in Peripheral Blood: A Promising Immune Index for Early Screening and Auxiliary Diagnosis of Colorectal Cancer - Lu, Yan; Zhang, Qiaohong; Zhang, Longyi (Frontiers in Oncology, 2021)
Background and Aims Colorectal cancer (CRC) lacks obvious symptoms in the early stage of the disease, making it is easy to be misdiagnosed and remain undetected. Here, we explored the role of CD4+ memory stem T cells (TSCM) in peripheral blood in the early screening and auxiliary diagnosis of CRC. Materials and Methods Patients diagnosed with a “colorectal mass” by colonoscopy, at the Dongyang People’s Hospital (Zhejiang, China), between November 2020 and June 2021, were included in this prospective study. Using histopathological results as the gold standard for diagnosis, patients were divided into “CRC group” and “benign tumor group”. Healthy volunteers were recruited as “healthy controls.” Ten-color flow cytometry was used to detect CD4+ T cell subsets, and the results were analyzed using the Kaluza software. Carcinoembryonic antigen (CEA) and carbohydrate antigen 199 (CA199) were detected by the Roche Cobas e 602 electrochemiluminescence immunoassay analyzer. Results This study involved 33 patients with CRC, 41 patients with colorectal benign tumors, and 49 healthy volunteers. The absolute value and frequency of CD4+ TSCM can clearly distinguish colorectal cancer, benign tumors, and healthy controls. According to the area under the receiver operating characteristic curve (AUC), the absolute value of CD4+ TSCM used to assist in the diagnosis of CRC was 0.758 (sensitivity: 0.612; specificity: 0.788), which is higher than the values for CEA (AUC: 0.707) and CA199 (AUC: 0.552). In early screening, the sensitivity of the absolute value of CD4+ TSCM (sensitivity: 0.612) was significantly higher than that of CEA (sensitivity: 0.333) and CA199 (sensitivity: 0.259). Conclusion CD4+ TSCM in peripheral blood may be a promising immune index for the early screening and auxiliary diagnosis of CRC.